2006
DOI: 10.2174/092986706778201503
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Cyclosporin-A in Spinal Cord Injury: An Overview

Abstract: Cyclosporin-A (CsA) is a potent and selective immunosupressive agent that, due to its mechanism of action, may be used to inhibit both the inflammatory reaction and the synthesis of nitric oxide (NO), a well-known neurotoxic agent. By these means CsA may diminish overproduction of free radicals and secondarily, lipid peroxidation (LP), both observed after acute spinal cord (SC) injury. Studies performed on reliable experimental models, using a well-standardized CsA dosing scheme, showed that a low dose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 107 publications
1
18
0
1
Order By: Relevance
“…As previously mentioned, animals in Group 2, containing PNIPAAm- g -PEG and the cell graft, received treatment with the cyclosporin A immunosuppressant, which reduces T cells and reduces the inflammatory resonse. 17,18,32 The responses were compared with Vitrogen PureCol with BDNF. The IBA-1 staining in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, animals in Group 2, containing PNIPAAm- g -PEG and the cell graft, received treatment with the cyclosporin A immunosuppressant, which reduces T cells and reduces the inflammatory resonse. 17,18,32 The responses were compared with Vitrogen PureCol with BDNF. The IBA-1 staining in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclosporin A can also act as a neuroprotective agent after SCI, as it can depress cellular and humoral immune responses by inhibiting T helper lymphocyte proliferation. 17,18,32 …”
Section: Methodsmentioning
confidence: 99%
“…This effect is probably reflected in a decrease of cell death mediated by free radicals (Ibarra and Diaz-Ruiz 2006). Previous studies have demonstrated that the use of antioxidant drugs able to inhibit lipid peroxidation attenuates the damage and improves motor function after SCI (Hamada et al, 1996;Diaz-Ruiz et al, 1999Bao et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…37 Cyclosporin-A is an immunosuppressant agent that has recently been demonstrated to have neuroprotective and neuroregenerative effects in SCI models. 38 Finally, baclofen is a centrally acting muscle relaxant used to treat spasticity. 31 The absorption of these drugs is significantly reduced when administered orally.…”
Section: Altered Pkmentioning
confidence: 99%